Paraneoplastic digital ischemia in clear-cell renal-cell carcinoma: Report of a case and review of the literature. Issue 3 (August 2019) - Kampoli, Katerina; Gardeli, Dimitra; Mouktaroudi, Maria; Fanouriakis, Antonis; Lazaris, Andreas M; Koumarianou, Anna
Digital ischemia has been rarely associated, as a paraneoplastic syndrome, with renal cancer. Since it can severely compromise the patients' quality of life, early recognition is important, in order to optimally address it with currently available treatment options, such as tyrosine inhibitors. Digital ischemia may occur in the general population and it can be the result of other non-cancerous diseases; accordingly, a thorough and aggressive work-up is mandatory, together with appropriate therapeutic steps such as tyrosine kinase inhibitors, vasodilators, and antiaggregants. Herein, we report a 78-year-old male patient with a history of clear-cell renal-cell cancer, who presented in the emergency department with critical ischemia in the upper limbs.